THE IMPACT OF URBANIZATION ON LANGUAGE USE IN DEVELOPING COUNTRIES - Qadamova Ruxshona Xabibulla qizi (TADQIQOTLAR.UZ, 2024)
Urbanization  has  become  a  significant  phenomenon  in  developing  countries, bringing about profound social, economic, and cultural transformations. One of the notable impacts of urbanization is its effect on language use. This article explores how rapid  urban  growth  influences  linguistic  practices,  particularly  in  the  context  of multilingual societies in developing nations. Urban centers become melting pots of diverse  linguistic  communities,  resulting  in  both  challenges  and  opportunities  for language maintenance, shift, and evolution.